Prosthetic rehabilitation of a patient submitted to segmental mandibulectomy (Research, Society and Development, 2022)
Surgical rehabilitation with grafts and plates of an oncological patient submitted to segmental mandibulectomy may be limited due to the majority receiving late diagnosis, requiring rapid intervention with association of drug therapies and thus, the risk of osteonecrosis. We detail a dental prosthetic rehabilitation in a patient who underwent a segmental mandibulectomy without plates or grafts. Man, 47-years old, affected by a squamous cell carcinoma on the floor of the mouth, treated by segmental mandibulectomy, radiotherapy and chemotherapy, was attended to a dental prosthetic rehabilitation over the mandible segments with a removable partial denture. Initially, a temporary prosthesis was made, in order to adapt the patient with the restoration of the occlusion and recovering the muscle tone. The patient used the temporary removable partial denture for 6 months, accompanied by physical therapy to maintain occlusal stability and regain muscle tone. After this period, it was possible to make a removable partial denture for definitive rehabilitation. The patient proved to be adapted to the prosthetic device and satisfied with the treatment. Prosthetic rehabilitation is a viable option when surgical reconstruction is contraindicated or can be used until the surgical procedure can be realized.